Peningkatan Kompetensi Pedagogik Mahasiswa Dalam Pengembangan Indikator, Tujuan Pembelajaran, Dan Instrumen Tes Berbasis Keterampilan Berpikir Tingkat Tinggi (High Order Thinking Skills) - Esomar, Ketarina; Nirahua, Juliana; Pulu, Sri Rahmadani (Pattimura University, 2022)
One of the profiles of graduates of the Unpatti FKIP Physics Education Study Program is to become a professional physics teacher. In line with that, one of the skills that must be possessed by a professional physics teacher is the ability to plan, design, and implement lesson plans, as well as evaluate learning processes and outcomes by applying logical, critical, systematic, and innovative thinking. Logical, critical, systematic, and innovative thinking in Bloom's taxonomy are the ability of higher order thinking skills (HOTS). The purpose of this study is to improve students' pedagogic competence in developing indicators, learning objectives, and HOTS-based test instruments. This type of research is Pre-Experimental Design in the One Group Pretest-post test design category, applied to 50 students of the Physics Education Study Program FKIP Unpatti in the fifth semester of the 2020-2021 academic year. Research data obtained through tests, performance, and non-test, processed descriptively using the normalized score gain formula. The average result of the increase is in the high category g = 0,76 ≥ 0,7. These results illustrate that there has been an increase in students' abilities in developing indicators, learning objectives, and developing HOTS-based test instruments. Development of indicators, learning objectives, test instruments and mastery of HOTS knowledge as part of the preparation of lesson plans and assessment of learning outcomes, taught as knowledge and strengthened in practice. In the exercise students are given the opportunity to identify forms of behaviour that can be observed, and measured at each level of cognition according to Bloom's taxonomy revised as a feature of HOTS, which are analysing, evaluating, and creating. In conclusion, increasing student pedagogic competence can be obtained through consistent mastery of knowledge and practice.